PERTANGGUNGJAWABAN PIDANA PENGURUS KOPERASI TERKAIT TINDAK PIDANA PERBANKAN DI BIDANG PERKOPERASIAN - SUGIANTARI, IDA SRI (Dinamika Hukum, 2020)
The purpose of this research is to examine and analyze the sitting case of a criminal offence at the Court of Law of Salatiga No. 10/Pid. Sus/2019/PN.Slt. Reviewing and analyzing the judgment of judges in breaking the lawsuit against the perpetrators of banking crimes at the verdict of the district Court of Salatiga No. 10/Pid. Sus/2019/PN.Slt. The method of approach in writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses the Skunder data. Data collection techniques using library studies. To analyze the data, researchers use qualitative descriptive analysis methods. Based on the results of the study obtained the conclusion that seated criminal act of banking at the decision of the District Court of Salatiga No. 10/Pid. Sus/2019/PN. Slt, Defendant has done gathering funds in the form of term deposits is not compatible with article 44 paragraph (1) of Law No. 25 of 1992 on the urban, where the principle contained in the provisions of the article is the funds collected must be from the member of the Cooperative. Legal fact at the conference showed that witnesses who deposit funds to KSP Multidana is not a member or prospective member of the KSP Multidana both at the head office of Ambarawa and the Office of Salatiga and the KSP Multidana it publishes the product of futures deposits with product specifications of the period of time, and interest rates, which are channeled to non-member and prospective members of the cooperative, the activity of collecting funds made by the defendant may be are specified as raising funds from the community in the form of deposits. Consideration of judges in breaking the lawsuit against the perpetrators of the banking criminal in the decision of District Court Salatiga No. 10/Pid. Sus/2019/PN. SLT which gives criminal sanctions to the defendant with imprisonment for 5 (five) years and a fine of Rp 10.000.000.000, 00 (ten billion Rupiah) with the provisions if the fine is not paid then replaced by criminal confinement for 3 (three) months according to the appropriate author, it is based on the indictment of the public Prosecutor is Violate Article 46 paragraph (1) Jo Article 16 paragraph (1) of the Law of the Republic of Indonesia Number 10 year 1998 concerning banking as a change to the law of the Republic of Indonesia number 7 year 1992 about banking, and consider the description of witnesses and expert witnesses. Keywords: Banking crimes, accountability of cooperative managers.